2014
DOI: 10.1039/c4ra06162d
|View full text |Cite
|
Sign up to set email alerts
|

Current perspective on bacterial pigments: emerging sustainable compounds with coloring and biological properties for the industry – an incisive evaluation

Abstract: International audienceThe current inclination towards exploiting bacterial pigments for various coloring functions, like food, cloth, painting, cosmetics, pharmaceuticals, plastics etc. is a well-recognized aspect. Nevertheless, the current bacterial pigment productions are not effective to meet their industrial needs. Current research going on world over on bacterial pigments signify that genetic engineering for strain improvement, optimization of bioprocess modelling and utilizing cheap agro-industrial resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 38 publications
0
44
0
1
Order By: Relevance
“…Among the various available pigments, the carotenoids alone are estimated to reach $1.4 billion by 2018 (Venil et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Among the various available pigments, the carotenoids alone are estimated to reach $1.4 billion by 2018 (Venil et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…While researchers such as Dufoss e et al 2014and Venil et al (2014aVenil et al ( , 2013 have identified the sustainability benefits of microorganism pigments and their advancements in fermentation in general, it is important to focus on particular pigment, yellowishorange pigment and examine its potential benefits and applications. This paper investigates the current challenges, economics, novel strategies and application of yellowish-orange pigment from microorganisms through exploratory reports and studies on this pigment.…”
Section: Methodsmentioning
confidence: 99%
“…As biotechnological industries are at the fast growth phase, shorter fermentation with high pigment yields is essential for industries. Advancement of microbiology was implemented by identifying bacterial strains with desired traits with the knowledge of biochemistry, chemical engineering and physiology (Venil et al, 2014a). Manipulation and alteration of sequence of genes in the DNA of bacterial strains were attempted to enhance the bacterial metabolism and increase the product yields.…”
Section: Genetic Engineering For Strain Improvementmentioning
confidence: 99%
See 2 more Smart Citations